Perbandingan Hasil Tangkapan Bagan Apung Berdasarkan Waktu Hauling Di Teluk Lasolo Kabupaten Konawe Utara - Fajeria -; Muslim Tadjuddah; Abdullah -; Naslina Alimina; Ahmad Mustafa (Universitas Halu Oleo, 2022)
The floating lift nets is one of the lifting nets that is operated in coastal waters at night using lighting aids from lights to attract the attention of fish that are positive phototaxis. The operation of the floating lift nets the fishermen usually carry out 2 transportation times each trip with a middle time night and after midnight. The purpose of this study was to determine the types of floating lift nets operated at different times, to determine the total weight of lift net catches operated at different times, to determine the best catch on floating lift nets operated at different times based on hauling time. This research was conducted in Lasolo Bay, Pasir-Putih Village, Lembo District, North Konawe Regency. Research was conducted from May to July 2022. The method used in this research is the actual fishing method. This study consisted of 2 treatments and 30 trips at midnight and after midnight based on hauling time. The data observed in the study included the total catch, weight per fish species, and type of composition. The data obtained were analyzed using independent t-test. The results showed that the total weight of the catch occurred more during the midnight catch and the highest catch was obtained on the 5-26.9 kg trip. The main catch obtained during the study was anchovy. It is necessary to extend the time between setting and hauling to allow fish to gather and adapt in the catchable area of the floating net. As well as the need for observations regarding the quality of the waters around the fishing area so that catches can increase.